Self Q-switching of a bismuth doped silica fiber operating at 1.46 mu m - Jung, Minwan; Lee, Ju Han; Lee, Sangbae; Lee, Kwanil (FIFTH ASIA-PACIFIC OPTICAL SENSORS CONFERENCE, 2015)
We demonstrate a self Q-switched Bismuth-doped germanosilicate fiber laser operating at 1463 nm. It is experimentally shown that stable Q-switched pulses with a temporal width of similar to 1.8 mu s can be obtained from a simple, all-fiberized Fably-Perot type cavity without using a saturable absorber at a a repetition rate of similar to 65 kHz with a pump power of similar to 260 mW. The tuning capability of the temporal characteristics of the output pulses is also investigated. The possible physical mechanism is discussed.